2018
DOI: 10.18352/ijc.856
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing processes in urban green commons. The case of the Angachilla wetland, Valdivia-Chile

Abstract: This article focuses on self-organizing processes in contested urban social-ecological systems. It analyzes a wetland conservation program and civic management effort in the Angachilla sector of the city of Valdivia, Chile in a 15-year time frame. The aim is to understand what triggers collective actions and self-organization in the attempts of preserving an urban green common. The study uses a qualitative approach based on action-research methodologies. It examines key variables influencing self-organizing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Leadership and social capital are seen as crucial in establishing a dialogue for conflict resolution, which was one of the common practices in this case. Strengthening the leadership could constitute a powerful tool [29,63], as this can establish goals, coordination activities, monitoring, dispute resolution, and sanctions [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership and social capital are seen as crucial in establishing a dialogue for conflict resolution, which was one of the common practices in this case. Strengthening the leadership could constitute a powerful tool [29,63], as this can establish goals, coordination activities, monitoring, dispute resolution, and sanctions [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in the presence of power asymmetries, communities may not be inclusive and may just replicate the existing local power inequalities [23,24]. On the other hand, scholars have also highlighted that the effectiveness or success of self-governed common resources depends on the community characteristics, such as size, community homogeneity, economic endowment, social and cultural aspects, and leadership [8,9,[25][26][27][28][29], and on external factors such as the political and social context, physical infrastructure, definition of property rights, and policy interventions [30][31][32][33]. As for community characteristics, for example, Luo et al [9] and Arvanitides et al [25] showed that smaller communities can create opportunities for interactions that, in turn, facilitate agreements and monitoring, thus increasing the chances for the community to engage in collective action.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a map with Valdivia's urban wetlands (in shaded areas), as showcased in a recent study by Paulina Ibieta [23]. Over the past few decades, citizens and community-based organizations have become increasingly concerned about the environmental impact of housing demands and illegal dumping on these natural habitats [24]. A pilot research project, aiming to investigate this issue from an acoustic perspective, was carried out.…”
Section: Wetland Soundscapesmentioning
confidence: 99%
“…Many contemporary commoning challenges are of this nature. Examples include the collective management of the natural environment (Rodgers et al 2012), the creation of complementary currencies (Meyer and Hudon 2017), identification of urban commons (Correa et al 2018;Unnikrishnan et al 2016), and the attribution of symbolic public goods such as nationalism (Rao 2008) or connection to the divine (Yue et al 2019).…”
Section: Institutional Dynamics In Contested Commonsmentioning
confidence: 99%
“…As these and other examples suggest, disagreements can exist about a commons. These can be related to several aspects such as its physical and symbolic delimitation, its multiple and competing uses (Correa et al 2018), property rights (Mukhopadhyay 2008), and, more broadly, its social meaning (Bardhan and Ray 2008;Yue et al 2019). Our study focuses specifically on the property regimes of commons.…”
Section: Institutional Dynamics In Contested Commonsmentioning
confidence: 99%